2015
DOI: 10.1016/j.rpor.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

SBRT: A viable option for treating adrenal gland metastases

Abstract: a b s t r a c tThe management strategy of adrenal metastases depends on different clinical situations.Adrenal metastasectomy in selected patients with isolated adrenal metastases is considered the treatment of choice, showing prolonged survival compared to chemotherapy alone.More recently, Stereotactic Body Radiation Therapy (SBRT) has emerged as an alternative local ablative treatment modality although limited data are available on the use of SBRT in treating adrenal gland metastases. Preliminary results are,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 38 publications
2
32
1
Order By: Relevance
“…The majority of adrenal metastases are accounted for by primary lung tumors, however breast, kidney, stomach, hepatobiliary carcinoma, and melanoma have also been found to metastasize to the adrenal glands [2,3]. Traditionally, local therapies like surgical resection or radiotherapy were reserved for palliation of symptomatic lesions, with external beam radiotherapy demonstrating good response rates and high rates of pain relief (40-80%) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of adrenal metastases are accounted for by primary lung tumors, however breast, kidney, stomach, hepatobiliary carcinoma, and melanoma have also been found to metastasize to the adrenal glands [2,3]. Traditionally, local therapies like surgical resection or radiotherapy were reserved for palliation of symptomatic lesions, with external beam radiotherapy demonstrating good response rates and high rates of pain relief (40-80%) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, many patients with adrenal gland metastases are considered medically inoperable due to severe comorbidities or the location or the extent of their metastases [16]. For these patients, stereotactic body radiotherapy (SBRT) offers an excellent, noninvasive treatment alternative [4,16].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, there has been increasing interest in the use of SBRT for the treatment of adrenal gland metastases. Review of ten studies including 188 patients reveals that 1-year local control ranged from 44 to 100%, and 1-year overall survival ranged from 39.7 to 90% [62]. Overall survival was mainly influenced by the development of widespread distant metastases.…”
Section: Nonsurgical Treatmentmentioning
confidence: 99%
“…Wardak et al, reported that the patient having lung cancer that they implemented SBRT for bilateral adrenal metastases developed adrenal insuf iciency depending on SBRT [6]. Ippolito et al, Reported that adrenal insuf iency may be due to both the tumor and the local treatment [12]. Incidence of symptomatic adrenal insuf iciency were reported 4% [2,13].…”
mentioning
confidence: 99%